Instituciones, procesos y desempeño en el abordaje de la calidad de la democracia en América Latina - Caldera Ortega, Alex Ricardo (SocietàMutamentoPolitica, 2018)
The article is a review of the evolution of the approach in political science that has focused on analyzing the institutional arrangements of contemporary political systems to generate stability, decisiveness, representativeness, decisiveness, accountability and results of public policies in democracy. Likewise, the current challenges of this analytical field in the Latin American context are reviewed.